Pengaruh Pemberian Sari Kacang Hijau dan Tablet Tambah Darah terhadap Peningkatan Kadar Hemoglobin pada Remaja Putri: The Effect of Giving Green Bean Extract and Blood-Adding Tablets on Increasing Hemoglobin Levels in Adolescent Girls - Hastuti Usman; Niluh Nita Silfia; Artika Dewie; Evi Mariani (Jurnal Bidan Cerdas, 2021)
Introduction: The incidence of anemia in women is 27.2% higher than men, 20.3%, mostly in the age group 15-24 years. The decrease in hemoglobin levels is caused by low intake of iron and other nutrients as well as the menstrual process. The coverage of giving blood tablets in Sigi Regency in 2019 was 81.25%. The purpose of this study was to determine the effect of giving green bean juice and blood-added tablets to increase hemoglobin levels in adolescent girls. Methods: Quasi-experimental research method with pretest-posttest control group design method. The population is young women aged 12 to 16 years with a total of 32 respondents. The research was conducted in the working area of ​​the Kinovaro Health Center. Results: The results of Hb levels in adolescent girls after being given the intervention of mung bean juice and added tablets are 2 g/dl with a p-value of 0.022, which means that there is a significant difference before and after giving green bean juice and blood-added tablets to the increase in hemoglobin levels of adolescent girls. Conclusion: Giving mung bean juice and blood-added tablets had a significant effect on increasing hemoglobin levels in adolescent girls. Suggestions are giving green beans and blood-added tablets once a week is very beneficial for young women in overcoming anemia.